Infusion Fluid Monitoring System Using Arduino Microcontroller and Internet of Think (IoT) to Increase Work Efficiency of Nurses in Hospital - Kadek Eka Swedarma; I Kadek Saputra; Fransiska Tri Mulyani Hastuti; Debbi Irfan Mudhoep (KHD-Production, 2023)
The occurrence of embolism and infiltration is still a significant problem in intravenous fluid therapy. An innovative product is needed to help nurses work properly. This study aimed to analyze the accuracy of digital monitoring programs for intravenous fluids in improving the work efficiency of nurses in hospitals. Research and Development design was employed in this study with the ADDIE Model approach. The digital system used an Arduino Microcontroller, Internet of Think, and displayed in an Android application. The study was conducted for three months; sixty-five, nurses from the General Hospital participated by purposive sampling technique. Each participant was given a questionnaire and logbook of infusion handling time. Data were analyzed by algorithm system, independent t-test, and paired t-test. The study showed that the accuracy of the infusion for 1 minute, 15 minutes, and 30 minutes is 99.5%. Most of the nurses were easy to use program application (77.14%), worked more efficiently (77.68%), decreased the average infusion handling time (4.06 minutes), and had a difference in the average time before and after the program implementation (p=0.002). Digital intravenous fluids monitoring systems can improve the work efficiency of nurses in hospitals. The application can be applied and become an innovative product reference for nursing.